2021
DOI: 10.1007/s13203-021-00263-1
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development and enhancement of cracking processes using metallic composites

Abstract: Metallic composites represent a vital class of materials that has gained increased attention in crude oil processing as well as the production of biofuel from other sources in recent times. Several catalytic materials have been reported in the literature for catalytic cracking, particularly, of crude oil. This review seeks to provide a comprehensive overview of existing and emerging methods/technologies such as metal–organic frameworks (MOFs), metal–matrix composites (MMCs), and catalytic support materials, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 119 publications
(182 reference statements)
0
2
0
Order By: Relevance
“…This can be due to their great potential and advantages like availability, environmental friendliness, abundance, cheap costs, non-toxicity and cation exchange ability. [22][23][24] For instance, in a study, the performance of kaolin-supported silver nanoparticles for the catalytic degradation of methylene blue (MB) in the presence of NaBH 4 was investigated. The experiments confirmed that the synthesized Ag-NPs/kaolin composite demonstrated high activity by removing 97 of MB dye.…”
Section: Introductionmentioning
confidence: 99%
“…This can be due to their great potential and advantages like availability, environmental friendliness, abundance, cheap costs, non-toxicity and cation exchange ability. [22][23][24] For instance, in a study, the performance of kaolin-supported silver nanoparticles for the catalytic degradation of methylene blue (MB) in the presence of NaBH 4 was investigated. The experiments confirmed that the synthesized Ag-NPs/kaolin composite demonstrated high activity by removing 97 of MB dye.…”
Section: Introductionmentioning
confidence: 99%
“…Clay minerals are one of the most extensively used classes of sorbents among any of these naturally occurring materials that are capable of absorbing ions [3]. The most important factor in the use of clay minerals is their ease of extraction and naturalness, low cost of production and durability and heat tolerance [4].…”
Section: Introductionmentioning
confidence: 99%
“…The activity and selectivity of the FCC catalyst are derived from the acidic sites and the pore structure, respectively. Catalytic catalysts are therefore porous solids with acidic properties [4,18,23]. Commercial FCC catalysts generally consist of two main components: the zeolite and the matrix.…”
Section: Introductionmentioning
confidence: 99%